Practical JRuby on Rails Web 2.0 Projects: Bringing Ruby on Rails to the Java™ Platform - Bini, Ola (Apress, 2012)
JRuby on Rails is an exciting technology. If you’ve picked up this book, you’ve probably realized the same thing. You might not have much experience with either Ruby or Rails, or you’ve tried both of them out and want to see why the combination of JRuby on Rails is so spectacular. Regardless of the reason, I hope this book will teach you something about some of the technologies involved, introduce you to new ways to look at problems, and help you see solutions in the intersection of languages where each one isn’t perfectly suited for a problem. I’ve been using Java for a long time, but my heart has never been in it. I’ve always been a programming language nerd, trying out new languages like my girlfriend tries new shoes. I knew what was out there, and that Java wasn’t the end-all solution for all the problems in the world. However, the fact remained that Java was the main language used for implementing systems during most of my employment. I compensated by continuing to have fun with other languages in my spare time. About three and a half years ago, I found Ruby. I can’t exactly remember how I did that, but I started using it and liked it very much. It combined some of the more useful parts of Lisp metaprogrammability, with a Smalltalky sensibility and cleanliness, while still retaining much of Perl’s pragmatism of doing whatever works.